2019
DOI: 10.1080/21645515.2019.1633878
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of candidate subunit vaccine and novel antitoxin against botulinum neurotoxin serotype E

Abstract: Botulinum neurotoxins (BoNTs) are among the most toxic proteins. Vaccination is an effective strategy to prevent botulism. To generate a vaccine suitable for human use, a recombinant non-His-tagged isoform of the Hc domain of botulinum neurotoxin serotype E (rEHc) was expressed in Escherichia coli and purified by sequential chromatography. The immunogenicity of rEHc was evaluated in mice and doseand time-dependent immune responses were observed in both antibody titers and protective potency. Then, the pilot-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In the last 20 years, the immunological significance of the Hc domain of BoNTs has been the subject of intensive research, leading to important findings [14][15][16][20][21][22][23][24][25]. Our research also indicated that the Hc domain is an effective protective antigen in subunit vaccines for BoNT/A, B, E, and F [26][27][28][29]. However, the immunogenicity of other regions requires further study, such as their protective efficacy and the synergistic effects of multiple epitopes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the last 20 years, the immunological significance of the Hc domain of BoNTs has been the subject of intensive research, leading to important findings [14][15][16][20][21][22][23][24][25]. Our research also indicated that the Hc domain is an effective protective antigen in subunit vaccines for BoNT/A, B, E, and F [26][27][28][29]. However, the immunogenicity of other regions requires further study, such as their protective efficacy and the synergistic effects of multiple epitopes.…”
Section: Discussionmentioning
confidence: 82%
“…To produce recombinant functional fragment antigens of BoNT/E in Escherichia coli, gene fragments of each function fragment (EL, EHN, EL-HN, EHc, EHc-N, and EHc-C, Table 1) were ligated into a prokaryotic expression vector, pTIG-Trx, to produce recombinant expression plasmids. As previously reported [26,36], our laboratory constructed pTIG-Trx prokaryotic expression plasmids encoding the following BoNT/E molecule fragments with His-tag: EL (residues 1-422), EHN (residues 423-840), EL-HN (residues 1-840), EHc-N (residues 841-1063), EHc-C (residues 1056-1252), and EHc (residues 841-1252). The resulting recombinant plasmids were confirmed by sequencing.…”
Section: Production Of Recombinant Functional Fragment Antigens Deriv...mentioning
confidence: 99%
See 1 more Smart Citation
“…twice with vaccines of different formulation. 20 TBV with Freund’s adjuvant (Sigma-Aldrich, Inc., St Louis, MO, USA) was prepared according the manufacturer’s instructions, in which complete Freund’s adjuvant (F5581) was used for the first immunization and incomplete Freund’s adjuvant (F5506) was used for the second immunization. A formulation without any antigens was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Sera from mice in different treatment groups were screened for anti-Hc antibody titer by ELISA as previously describe. 20 Sera antibody titers of individual mice were assayed, and the geometric mean titer (GMT) for each group was determined.…”
Section: Methodsmentioning
confidence: 99%